An optimization methodology for self-consumption of residential photovoltaic energy. Issue 2 (2020) - Amabile, Loris; Bresch-Pietri, Delphine; Hajje, Gilbert El; Labbe, Sébastien; Petit, Nicolas
Abstract: This paper considers the optimization of the self-consumed power locally produced by residential photovoltaic panels. We focus on a simplified set-up where only the Electric Water Heater (EWH) is regulated, while the rest of the appliances represents an uncontrollable load. We formulate an unconstrained optimization problem by inverting the EWH dynamics and prove that the corresponding objective function is continuously differentiable. Thanks to an explicit characterization of its critical points, we propose a tailored and computationally efficient optimization algorithm. Simulations performed in Dymola over a one-year time horizon allow us to demonstrate the merits and performances of the proposed method.